Proses Produksi Video Kegiatan Pemerintah Kota Bogor Di Akun Instagram @Pemkotbogor Sebagai Media Komunikasi Publik - Salma Dhiyayl Haq; Guruh Ramdani (Professional: Jurnal Komunikasi dan Administrasi Publik, 2026)
This study aims to examine the video production process for Bogor City Government activities published via the @pemkotbogor Instagram account and to understand the role of these videos as a medium of public communication. This study employs a descriptive qualitative method, utilizing data collection techniques such as interviews, observation, and documentation within the Broadcasting Division of the Information and Public Communication (IKP) Department at the Bogor City Communication and Information Agency (Diskominfo). The research analysis employs the audiovisual production framework by Gerald Millerson and Jim Owens, which encompasses pre-production, production, and post-production stages, and is supported by the concept of Public Service Broadcasting to examine the function of videos as a medium for public information services. The findings reveal that the video production process is conducted in a structured manner, beginning with conceptual planning, equipment preparation, filming of government activities, and editing before publication on Instagram. In this process, the Broadcasting Division not only focuses on audiovisual technical aspects but also on the clarity of information and the public’s need for accurate and easily understandable public information. This study demonstrates that government activity videos published via the @pemkotbogor Instagram account serve as a digital public communication medium that supports the rapid, visual, and easily accessible dissemination of government information to the public.